Madeleine Collins [videorecording (DVD)] - Barraud, Antoine; Efira, Virginie, 1977-; Gutiérrez, Quim, 1981-; Salomone, Bruno, 1970-; Benguerel, Loïse; Bisset, Jacqueline, 1944-; Donzelli, Valérie; Lapid, Nadav, 1975-; Gioria, Thomas; Rostain, François; Boutefeu, Nathalie; Walravens, Mona, 1986- (Greenwich Entertainment, 2023)
"In this tense psychological drama, Judith leads a secret double life split between two households in two countries. In Switzerland, she lives with Abdel, with whom she is raising a little girl. In France, she lives with Melvil, with whom she has two older boys. Gradually this fragile balance, based on lies and back-and-forth trips, begins to veer dangerously off the rails"--From container.